Budgeting in Italy - Blöndal, Jón R.. (OECD Publishing, 2016)
Italy is in the process of making significant reforms to its budgeting process. This report provides a comprehensive overview of the Italian budgeting system and the envisaged reforms. It also offers a number of specific recommendations for further consideration as Italy advances its reform agenda. The report has been peer reviewed by OECD Senior Budget Officials. JEL Classification: H50, H61, H83, O52 Keywords: Italy, Stability Law, spending reviews, medium-term expenditure frameworks